Analisis Kriminologis Terhadap Transaksi Jual Beli Secara Ilegal Minuman Keras Di Amarasi Selatan, Kabupaten Kupang - Mahmud, Faishol Reza; Wilhelmus, Bhisa Vitus; Amalo, Heryanto (Law Faculty, Nusa Cendana University, 2024)
The flow of liquor proper now's quite huge due to the fact almost in each location in the jurisdiction of Indonesia there are many places that sell alcoholic drinks. this could be visible via the developing sort of places that offer, and distribute alcoholic drinks on an commercial / manufacturing facility and domestic scale. this may be visible with the aid of way of the developing quantity of places that offer, and distribute alcoholic drinks on an commercial / factory and home scale. Transactions of buying and selling alcoholic drinks that arise, are achieved freely with out regard to the risks and facet results induced. Poorly considered and accurate thresholds for alcohol use, are very unstable to eat. With the method of the trouble of this studies is: (1) what is the modus operandi of liquor buying and promoting transactions that arise in South Amarasi, Kupang Regency? (2) what's the effect of liquor purchasing for and selling transactions on the level of crime and offences devoted in South Amarasi, Kupang Regency? This studies is an empirical juridical studies approach, particularly prison research at the enactment or implementation of normative criminal provisions in motion on positive felony events that arise in society. The effects of this have a take a look at display: (1) To apprehend and deliver an reason for the modus operandi of buying and promoting alcoholic liquor transactions in South Amarasi, Kupang Regency. (2) To determine and provide an explanation for the impact of liquor looking for